Dampak Ekonomi Pengembangan Agro Wisata Sirah Kencong Pada Pekerja PTPN XII Blitar (Economic Impact of the Development of Sirah Kencong Agro-Tourism on PTPN XII Blitar Workers) - Elyani, Elyani; Ganefo, Akhmad (Jurnal ENTITAS SOSIOLOGI, 2020)
The purpose of this study was to describe the economic impact of agro-tourism development on PTPN XII plantation workers Sirah Kencong Blitar. The method used is qualitative. Determination of informants is using purposive sampling techniques. In this study, informants are community leaders (RT / RW), village elders or people who have lived in the Sirah Kencong tea plantation area, local government, tourism management, and several residents concerned in the management of the tourism area. Data collection techniques are done by observation, in-depth interviews, and documentation. Test the validity of the data using triangulation techniques. The analysis technique uses an interactive model. The theory used is the Cohen Tourism Socio-Economic Impact theory. The results showed that: 1) The development of agrotourism had economic and social impacts as a continuation for the community, namely in the financial aspect made the increase in job vacancies and increased income from various employment sectors related to tourism 2) the development of the economic sector, such as stalls, shops, souvenir merchants, etc. 3) For the social aspects of the development of Sirah Kencong agro-tourism, there are several impacts for the community, namely increasing the ability of the community in the field of tourism, in social aspects, they become more understanding of how to dress well, communicate well, and also the level education is increasing because of the development of tourism. So, based on the research results of agro-tourism development, it has a positive impact on the lives of PTPN XII plantation workers Sirah Kencong Blitar. Keywords: Economic Impact, Social Impact, Agro-tourism, Plantation Workers Tujuan penelitian ini adalah untuk mendeskripsikan dampak ekonomi pengembangan agrowisata terhadap pekerja perkebunan PTPN XII Sirah Kencong Blitar. Metode yang digunakan adalah kualitatif. Penentuan informan menggunakan teknik purposive sampling. Dalam penelitian ini informan adalah tokoh masyarakat (RT/RW), sesepuh desa atau masyarakat yang pernah tinggal di kawasan perkebunan teh Sirah Kencong, pemerintah daerah, pengelola wisata, dan beberapa warga yang berkepentingan dalam pengelolaan kawasan wisata. Teknik pengumpulan data dilakukan dengan observasi, wawancara mendalam, dan dokumentasi. Uji validitas data menggunakan teknik triangulasi. Teknik analisis menggunakan model interaktif. Teori yang digunakan adalah teori Dampak Sosial Ekonomi Pariwisata Cohen. Hasil penelitian menunjukkan bahwa: 1) Pengembangan agrowisata memberikan dampak ekonomi dan sosial sebagai kelanjutan bagi masyarakat yaitu dalam aspek keuangan membuat peningkatan lapangan kerja dan peningkatan pendapatan dari berbagai sektor pekerjaan yang terkait dengan pariwisata 2) pengembangan bidang ekonomi, seperti warung, toko, pedagang cinderamata, dll 3) Untuk aspek sosial pengembangan agrowisata Sirah Kencong ada beberapa dampak bagi masyarakat yaitu peningkatan kemampuan masyarakat dalam bidang pariwisata. Dalam aspek sosial, mereka menjadi lebih memahami cara berpakaian yang baik, berkomunikasi yang baik, dan juga tingkat pendidikan yang meningkat karena perkembangan pariwisata sehingga berdasarkan hasil penelitian pengembangan agrowisata berdampak positif bagi kehidupan pekerja perkebunan PTPN XII Sirah Kencong Blitar. Kata kunci: Dampak Ekonomi, Dampak Sosial, Agrowisata, Pekerja Perkebunan